Pengelolaan Wisata Berbasis Kearifan Lokal Dengan Menggunakan Media Sosial Sebagai Promosi di Desa Belitar Seberang - Curup - Astuty, Kamelia; Nurzam, Nurzam; Sudarsono, Aji; Kurniawan, Kimas; Novitasari, Meise (Universitas Dehasen Bengkulu, 2023)
Each region in Indonesia has different local wisdom and has its own beauty and has the values ​​contained therein. One of them is Local Wisdom in Belitar Seberang Village - Curup which is one of the leading tourist destinations with beautiful nature as one of the main attractions in Sindang Kelingi District, Rejang Lebong Regency, Bengkulu Province which has made it into the top 50 villages the best tour at the Indonesian Tourism Village Award Event (ADWI) in 2022 and was immediately appreciated by the Minister of Tourism and Creative EcoEach region in Indonesia has different local wisdom and has its own beauty and has the values ​​contained therein. One of them is Local Wisdom in Belitar Seberang Village - Curup which is one of the leading tourist destinations with beautiful nature as one of the main attractions in Sindang Kelingi District, Rejang Lebong Regency, Bengkulu Province which has made it into the top 50 villages the best tour at the Indonesian Tourism Village Award Event (ADWI) in 2022 and was immediately appreciated by the Minister of Tourism and Creative Economy/ Head of the Tourism and Creative Economy Agency (Menparekraf/Kabaparekraf) Sandiaga Salahuddin Uno during a direct visit to the Belitar Seberang Tourism Village. He said this achievement was the result of good collaboration between the community which was coordinated with the local tourism awareness group (Pokdarsi) and supported by the District Government, Provincial Government and Central Government. Belitar Seberang Village offers unique natural, man-made and cultural tourism, and is supported by complete facilities. This study aims to determine tourism management based on local wisdom in supporting sustainable tourism in Rejang Lebong Regency and to introduce tourist attractions in Belitar Seberang Village, which is located in Rejang Lebong Regency. The selection of the research location was carried out using the platform method via social media.nomy/ Head of the Tourism and Creative Economy Agency (Menparekraf/Kabaparekraf) Sandiaga Salahuddin Uno during a direct visit to the Belitar Seberang Tourism Village. He said this achievement was the result of good collaboration between the community which was coordinated with the local tourism awareness group (Pokdarsi) and supported by the District Government, Provincial Government and Central Government. Belitar Seberang Village offers unique natural, man-made and cultural tourism, and is supported by complete facilities. This study aims to determine tourism management based on local wisdom in supporting sustainable tourism in Rejang Lebong Regency and to introduce tourist attractions in Belitar Seberang Village, which is located in Rejang Lebong Regency. The selection of the research location was carried out using the platform method via social media.